Analisis Modal Kerja untuk Peningkatkan Produktivitas pada PT. Unilever Indonesia, Tbk. Periode 2006-2010 - Gani, Engelwati (Binus Business Review, 2012)
The study was conducted at PT. Unilever Indonesia, Tbk, which aims to determine the level of working capital management and corporate productivity. Quantitative analysis methods used and data analysis techniques used are the working capital analysis, financial ratio analysis and the analysis of the productivity ratio. Research results obtained from the results that a decrease in working capital at PT. Unilever Indonesia, Tbk. from the year 2006-2010 which decreases the amount of current assets while current liabilities increased. PT levels of liquidity. Unilever Indonesia, Tbk. is also quite low and has decreased every year. Expected PT. Unilever Indonesia, Tbk. able to increase the amount of current assets to cash and cash equivalents productivity is not compromised. Productivity ratio of PT. Unilever Indonesia, Tbk in 2010 has increased due to production cost savings and increased sales obtained. This suggests a tight working capital management is carried out by PT. Unilever Indonesia, Tbk. can increase company productivity.